Turkish neoimperial activities on the example of Syria and Syrian civil war - Religa, Wojciech (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
The purpose of present article is checking what impact on Middle East region and the Republic of Türkiye itself, was exerted by declarations and behaviour of postislamic party called Justice and Development Party (AKP), which leader Recep Tayyip Erdoğan has ruled Türkiye indivisibly since 2002 until today. It will be done using comparative method, by comparing AKP’s activities with anticipatory reigns of bureaucratically-military elite of Kemalists whose unofficial patronage on Turkish state lasted since the beginning of Republic of Turkey. That comparison involves also socio-political strategies, which were used by AKP before and after Arab Spring, which changed Middle East region forever. Particular emphasis of those activities will be involved in Turkish-Syrian relationship because Syrian Arab Republic was a subject of particular Ankara’s attention both before and after Erdoğan gained power. Moreover, in my work it will be described how Erdoğan’s supporters were reacting to the waves of Syrian refugees who are flowing to Türkiye and Ankara’s attitude to Kurds societies, especially Syrian Kurds and relationship between AKP and terrorists from Islamic State of Iraq and the Levant (ISIS) who are fighting both with Kurds and Bashar al-Asad regime. It is because those three socio-international operations are the best example of using Syrian factor by Ankara to realise geopolitical ambitions of Turkish leader Recep Erdoğan.